The art of Homer and the historian: introductory remarks - Neto, Félix Jácome (Romanitas - Revista de Estudos Grecolatinos, 2013)
This article tends to summarize some specific literary features of the Homeric poems – Iliad and Odyssey – in which a historical approach has to be in accordance with the type of discursive narrative which works in the cultural context that influences the production of Homeric epic. The obscure and highly disputed evidence on early stages about the production and transmission of the poems and also the specific stylistic dispositive from oral derived text distinct to our modern literature concept are challenges that the historian must be aware in order to formulate their hypotheses work more consistently. Thereby, this article offers an overview of these issues while suggests further reading for a more accurate deepening.
Keywords: Homer; Oral Theory; Homeric poems